Studi Tematik Hadis Tentang Hubbullah dalam Tinjauan Teologi - Siti Haeriah; Rafli Ahmad Falevi; Reva Hudan Lisalam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to discuss the hadiths regarding hubbullah. The method used in this study is a qualitative type which interprets the matan (text) using the thematic method approach (maudhu'i). The results of the discussion include the meaning and urgency of hubbullah, various forms of love in Islam, and hadiths related to hubbullah. The love of a servant to Allah must exceed his love for himself and his parents, siblings, friends, and others. Hubbullah itself is a form of a servant's faith in Allah and His Messenger, also loving fellow creatures on earth and the universe. With love for Allah and obedience and obedience to all His commands and prohibitions, a person will not care about the world more than his Lord. God has arranged everything that happens on this earth so that humans can go through everything that God has given. This research concludes that the hadiths related to hubbullah teach spiritual values to love God more than the world.